Personality Characteristics in Schoolteachers’ Occupational Motivation - Oleg KOKUN; Liudmyla SERDIUK; Viktor VUS (European Journal of Interdisciplinary Studies, 2025)
Because schoolteachers’ high occupational motivation is an essential prerequisite for their good performance, it is important to understand the personality characteristics that determine it. The present study involved 188 primary and secondary schoolteachers from three regions of Ukraine. Data collection relied on Zamfir’s Motivation for Professional Activities technique, the General Self-Efficacy Scale, the Personal Orientation Inventory, the communicative inclinations sub-test of the method identifying communicative and organisational inclinations, the Professional Self-Fulfilment Questionnaire and the Maslach Burnout Inventory General Survey. The data obtained showed that nine out of 10 personality characteristics used in our study significantly influenced schoolteachers’ occupational motivation. Of these, seven variables had a positive effect, contributing to schoolteachers’ intrinsic motivation, but two indicators of occupational burnout (personal accomplishment and emotional exhaustion) had a negative effect, reducing motivation. The most significant personality characteristics were communicative inclinations (explaining 16.6% of the variation in intrinsic motivation), personal accomplishment (9.3%) and self-efficacy (6.0%). Six additional indicators – three indicators of professional self-fulfilment and individual indicators of time competence, emotional exhaustion and inner-directed support – explained schoolteachers’ intrinsic motivation within 2.7–4.3% limits. A multiple regression analysis revealed that the set of 10 personality characteristics used in our study was highly informative (R = .503; R2 = .253), explaining 25.3% of schoolteachers’ intrinsic motivation. The results open up new perspectives to increase and stabilise schoolteachers’ occupational motivation.